Effect of barium and lanthanum oxides on the properties of Pt/KL catalysts in the n-heptane dehydrocyclization - Grau, Javier Mario (2000)
Six fractions of zeolite KL were impregned with 1, 3 and 5 wt% of Ba or La, respectively, with nitrate precursors aqueous solutions. After calcination at 873 K to form BaO or La2O3, 1 wt% of Pt was incorporated to the supports by the impregnation method. Metal dispersion decreases as the Ba concentration increases, but it is not substantially affected by the La addition. The CO/FTIR and the competitive hydrogenation of benzene + toluene results indicate that an electron enrichment of the Pt particles occurs by effect of the additives. The increase of the electron density of Pt in Ba-catalysts is higher than for the La-catalysts. Moreover, the Ba addition highly enhances the aromatization and terminal hydrogenolysis activities, without substantial modification of the yields to the other reaction products. The yield to toluene is also increased by effect of 1 wt% of La, but it does not increases with the La concentration. The TEM-EDX studies indicate that the different distribution of the BaO and La2O3 in the zeolite may be the origin of the different surface and catalytic effects of these oxides in the Pt/KL catalysts.